Demand Response based Trading Framework in the Presence of Fuel Cells Using Information-Gap Decision Theory - Vahid-Ghavidel, Morteza; Javadi, Mohammad Sadegh; Santos, Sérgio F.; Gough, Matthew; Shafie-khah, Miadreza; Catalão, João P. S. (IEEE, 2020)
Nowadays demand response (DR) is known as one of the main parts of the power system especially in the smart grid infrastructure. Furthermore, to enhance the participation of the consumers in the DR programs, the Independent System Operators (ISOs) have introduced a new entity, i.e. Demand Response Aggregator (DRA). The main contribution of this paper is to investigate a novel framework to increase the profits of the DRA participating in the day-ahead electricity market, i.e. employment of an axillary generation system in the DRA entity. It is supposed that the DRA in this paper has an axillary generation system and it would lead to an increase in the profit of the DRA through avoiding the economic loss in the process of trading DR obtained by the active participation of prosumers in the electricity market. The fuel cell is introduced as the axillary generation unit to the DRA unit. In the framework proposed in this paper, the DR is acquired from end-users during peak periods and will be offered to the day-ahead electricity market. The power flow during the off-peak hours is in another direction, i.e. from the grid to the consumers. In this model, the information-gap decision theory (IGDT) is chosen as the risk measure. The uncertain parameter is the day-ahead electricity market price. The optimization problem's objective is to maximize the profit of the DRA. The behavior of the risk-seeker decision-maker is analyzed and investigated. The feasibility of the program is demonstrated by applying it to realistic data.
Keywords: demand response aggregator (DRA); Demand response (DR); fuel cell; information-gap decision theory (IGDT); risk management; uncertainty; fi=Sähkötekniikka|en=Electrical Engineering|